THE PHONINESS IN THE NOVEL THE CATCHER IN THE RYE BY J.D. SALINGER - Salsabila Fajrina Rizal (Linguistika Kultura, 2023)
This research seeks to explain why Holden believes everyone is a liar, why conflicts emerge between novel characters, and how rivalry affects the characters in J.D. Salinger's The Catcher in the Rye. All these things caused the main character in the novel to alienate himself from society, and this conflict forced him to suffer from depression and be hospitalized. This journal study uses a descriptive qualitative method approach. The main character suffers from an imbalanced mental life. Therefore, this study will answer the question of Holden's means of phoniness, based on his view as 1.) Holden's protection of innocence, 2.) Holden's hatred for the phoniness of the adult world, and 3.) Holden's isolation as a result of his self-protection from the phoniness world. Keywords: adolescent difficulties, innocence, alienation, phoniness